Evaluating the effectiveness of immediate vs. elective thoracic endovascular aortic repair for blunt thoracic aortic injury - Zhaohui Hua; Baoning Zhou; Wenhao Xue; Zhibin Zhou; Jintao Shan; Lei Xia; Yunpeng Luo; Yiming Chai; Zhen Li (Chinese Journal of Traumatology)
Purpose: To evaluate the relationship between the timing of thoracic endovascular aortic repair (TEVAR) for blunt thoracic aortic injury (BTAI) and prognosis. Methods: This is a single-center retrospective cohort study. Patients who received TEVAR for BTAI at our institution from October 2016 to September 2023 were divided into 2 categories depending on the injury severity score (ISS) (≤ 25 vs. > 25) and when the TEVAR was performed for BTAI (within 24 h vs. after 24 h), respectively. The analysis included all patients who received TEVAR treatment after being diagnosed with BTAI through whole-body CT angiography. Patients treated with open repair and non-operative management were excluded. After propensity-score matching for various factors, outcomes during hospitalization and follow-up were compared. These factors included demographics, comorbidities, concomitant injuries, cause and location of aortic injury, Glasgow coma scale score, society for vascular surgery grading, hemoglobin concentration, creatinine concentration, shock, systolic blood pressure, and heart rate at admission. The comparison was conducted using SPSS 26 software. Continuous variables were presented as either the mean ± standard deviation or median (Q1, Q3), and were compared using either the t-test or the Mann-Whitney U test. Categorical variables were expressed as n (%), and comparisons were made between the 2 groups using the χ2 test or Fisher’s exact test. Statistical significance was defined as a 2-sided p < 0.05. Results: In total, 110 patients were involved in the study, with 65 (59.1%) patients having ISS scores > 25 and 32 (29.1%) receiving immediate TEVAR. The perioperative overall mortality rate in the group with ISS > 25 was significantly higher than that in the group with ISS ≤ 25 (11 (16.9%) vs. 2 (4.4%), p < 0.001). Upon admission, the elective group exhibited a notably higher Glasgow coma scale score (median (Q1, Q3)) compared to the immediate group (15 (12, 15) vs. 13.5 (9, 15), p = 0.039), while the creatinine concentration (median (Q1, Q3)) at admission was significantly higher in the immediate group (90.5 (63.8, 144.0) vs. 71.5 (58.3, 80.8), p = 0.012). The final sample included 52 matched patients. Complications occurred significantly less frequently in the elective group compared to the immediate group (16 (50.0%) vs. 3 (10.0%), p < 0.001). Single-factor analysis of variance showed that complications in hospitalized patients were significantly associated with immediate TEVAR as the sole independent risk factor (odds ratio: 9.000, 95% confidence interval: 2.266–35.752, p = 0.002). Conclusion: In this propensity-score matched analysis of patients undergoing TEVAR for BTAI, elective TEVAR was significantly associated with a lower risk of complication rates. In this study using propensity-score matching, patients who underwent elective TEVAR for BTAI had lower complication rates than immediate TEVAR.